Influences of the metastability of austenitic stainless steels on the wear behavior in a radial shaft seal system - Tong Zhu; Marek Smaga; Tim Schollmayer; Christoph Burkhart; Oliver Koch; Stefan Thielen; Tilmann Beck (Journal of Materials Research and Technology)
Wear tests were conducted on shafts manufactured from three commercial austenitic stainless steels – AISI 303, 347, 904L – within the context of a sealing contact of radial shaft seal system, where wear resistance is critical to preventing leakage. Although austenitic stainless steels are favored for their corrosion resistance, they are often limited by poor tribological properties due to their low hardness. However, their unique property of metastability enables microstructural mechanisms such as deformation-induced α′-martensite transformation, twinning, and dislocation slip, which can lead to additional work hardening and, consequently, influence wear performance. Despite contradictory reports on the role of these mechanisms in wear behavior, austenitic stainless steels remain indispensable in corrosive environments, emphasizing the need for a deeper understanding of their behavior under tribological loading. This study investigates the influence of metastability on wear resistance in radial shaft seal applications by comparing metastable and stable austenitic stainless steels with different surface morphologies. Compared to the case-hardened AISI 5110 carbon steel benchmark, both metastable steels AISI 303 and AISI 347 exhibited comparable wear resistance despite significantly lower hardness values. Meanwhile, deeper wear tracks were observed on the stable AISI 904L shafts. Additionally, the shaft surfaces were investigated in both non-hardened and work-hardened states: plunge-ground and hard-turned, respectively. It has been proved that regardless of the different initial surface conditions, the metastability of the austenite phase significantly influenced the wear performance of the machine components. Systematic surface characterization was carried out to elucidate the crucial influence of local microstructural changes on wear performance, including the presence of a nanocrystalline layer, martensitic phase transformation, as well as work-hardening in the austenite grains. These findings highlight the importance of metastability-driven microstructural changes in improving wear resistance, offering valuable guidance for material selection and surface engineering in sealing applications.